A case study of parking charges at work places: Effects on travel behaviour and acceptance - Christiansen, Petter (Proceedings from the Annual Transport Conference at Aalborg University, 2014)
This paper analyse how a parking fee affect modes of transport on work travels and how acceptability varies over time among employees. The findings shows that the share of car drivers is reduced from 35 to 27 percent after the fee was introduced. There are weak tendencies towards spill-over parking and the fee has contributed to less need for employees to arrive early in order to secure a parking space. The acceptance for the parking fee changed from being negative before the fee to positive one year after the fee.